The Unique Helium Nova V445 Puppis Ejected ≫0.001 M⊙ in the Year 2000 and Will Not Become a Type Ia Supernova - Bradley E. Schaefer (The Astrophysical Journal)
V445 Puppis (Nova Puppis 2000) is the only known example of a helium nova, where a layer of helium-rich gas accretes onto the surface of a white dwarf (WD) in a cataclysmic variable, with runaway helium burning making for the nova event. Speculatively, a helium nova can provide one path to produce a Type Ia supernova (SNIa), within the larger framework of single-degenerate models. Relatively little has been known about V445 Pup, with this work reporting the discovery of the orbital period near 1.87 days. The companion star is 2.65 ± 0.35 R _⊙ in radius as an evolved giant star stripped of its outer hydrogen envelope. The orbital period immediately before the 2000 eruption was ${P}_{{\rm{pre}}}$ = 1.871843 ± 0.000014 days, with a steady period change of (−0.17 ± 0.06) × 10 ^−8 from 1896 to 1995. The period immediately after the nova eruption was P _post = 1.873593 ± 0.000034 days, with a $\dot{P}$ of (−4.7 ± 0.5) × 10 ^−8 . The fractional orbital period change (Δ P / P ) is +935 ± 27 ppm. This restricts the mass of the gases ejected in the nova eruption to be ≫0.001 M _⊙ , and much greater than the mass accreted to trigger the nova. So the WD is losing mass over each eruption cycle, and will not become a SNIa. Further, for V445 Pup and helium novae in general, I collect observations from 136 normal SNIa for which any giant or subgiant companion star would have been detected, yet zero companions are found. This is an independent proof that V445 Pup and helium novae are not SNIa progenitors.